ASSESSMENT OF NATURAL RADIOACTIVITY LEVELS AND RADIATION HAZARDS IN RAW MATERIALS USED FOR CEMENT PRODUCTION AT ASHAKA CEMENT COMPANY - A. D, BAJOGA; Y. M, DAWAKI; H, SEYDOU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Natural radioactivity levels from sixteen samples due to radionuclides present in Limestone, Gypsum, Fly-Ash and Iron-Ore, used in cement production at Ashaka cement company were determined, employing gamma-ray spectrometry technique involving NaI(Tl) detector. Measurements and analysis were carried out and the mean radioactivity concentrations due 226Ra (238U), 232Th and 40K from the materials were found to range from (11.27 – 16.76) Bq/kg, (13.76 – 35.73) Bq/kg and (117.23 - 212.00) Bq/kg, with an average value of 14.95 Bq/kg, 21.04 Bq/kg, and 168 Bq/kg, respectively. Radiological risk indices associated with the above results, i.e. Radium equivalent (Raeq), internal (Hin) and external (Hex) hazards, Absorbed dose (D), Annual effective doses (AEDE), Life time cancer risk (LCR) were also computed. The mean results obtained indicate the following: Raeq = 59.65 Bq/Kg, D = 27.45 nGy/hr, Hin = 0.77, Hex = 0.16, AEDEindoor = 0.045, AEDEoutdoor = 0.011, LCRindoor = 0.105, and LCRoutdoor = 0.026. The largest contribution to total mean activity of 238U, 232Th and 40K among the samples come from Fly-Ash, Gypsum, Iron-Ore and Limestone, at 76%, 85% and 80%, respectively. Also, a good correlation of 0.95 between activity of 238U and 232Th was observed in the samples. The highest and lowest absorbed doses determined are from Gypsum and Limestone at 37.77 nGy/hr and 22.08 nGy/hr, respectively. The results obtained indicates that the materials are safe to be used as components of building construction based on limits set by international scientific and regulatory agencies including ICRP, IAEA and UNSCEAR.